High-efficiency non-halogenated solvent processable polymer/PCBM solar cells via fluorination-enabled optimized nanoscale morphology. Issue 43 (18th October 2019) - Rasool, Shafket; Hoang, Quoc Viet; Van Vu, Doan; Trang Bui, Thi Thu; Jin, Seon-Mi; Ho, Thuy Thi; Song, Chang Eun; Lee, Hang Ken; Lee, Sang Kyu; Lee, Jong-Cheol; Moon, Sang-Jin; Lee, Eunji; et al.
Abstract : The fullerene-based PSCs based on novel PNTz4T-1F polymer processed from a halogen-free solvent system demonstrated an outstanding PCE of 11.77% due to the optimum molecular ordering/packing and morphology. Abstract : PNTz4T-based polymers have been extensively employed in high-efficiency fullerene-based polymer solar cells (PSCs) with a power conversion efficiency (PCE) of approximately 10.0% due to the high crystallinity of these polymers. The introduction of two fluorine atoms into PNTz4T to synthesize the PNTz4T-2F polymer has boosted the PCE to 10.6%, but the introduction of four fluorine atoms to synthesize the PNTz4T-4F polymer negatively affects the efficiency (PCE = 6.5%), implying that the number of fluorine atoms is not yet optimized. We have developed a new synthetic route for a novel monofluoro-bithiophene monomer and successfully synthesized a novel PNTz4T-1F polymer. The fullerene-based PSCs based on our novel PNTz4T-1F polymer processed using a halogen-free solvent system demonstrated an outstanding PCE of 11.77% (11.67% certified), representing the highest PCE reported thus far in the literature. Due to the optimum molecular ordering/packing, improved interaction with PC71 BM and interconnectivity between photoactive material domains, PNTz4T-1F-based PSCs exhibit lower charge carrier recombination and enhanced charge carrier mobility levels, leading to a substantially high photocurrent density (20.37 mA cm −2 ). These results create new means to tune the structural properties of polymers, ultimately leading to the realization of this class of solar cells for practical applications.